PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP TURNOVER INTENTION KARYAWAN: STUDI KASUS PADA PT. ANDALAN INFORMASI TEKNOLOGI - Fatari Fatari; Wahyu Wiguna (LP2M Universitas Bina Bangsa, 2023)
This study aims to determine the compensation and work motivation variables, partially and simultaneously on turnover intentions. This study uses a survey method using quantitative with the number of respondents 48 employees from 92 number of employees. Based on the results of the t test or partially showed a variable compensation and work motivation significantly to employee turnover intention. This is evidenced based on the results of the t test (partial) where in the results of these results indicate the t value of the compensation variable of 4.024 and t calculate the work motivation variable of 2.971, known t table of 2.014, from the independent variable of t table. Simultaneously the two variables are aimed at turnover intentions, this is evidenced by the results of the F test where the output results show the calculated F value of 15.855 and F table of 3.20. The conclusion of this study, both partially and simultaneously shows that the compensation and work motivation variables are highly variable on the employee turnover intention of PT. Andalan Informasi Teknologi